A Randomized Controlled Trial on the Influence of Prenatal Counseling on the Attitudes and Preferences Toward Invasive Prenatal Testing Among Women in Their First Trimester of Pregnancy (INVASIVE) - Paz y Miño, Fernanda; Martinez-Portilla, Raigam Jafet; Pauta, Montse; Borrell, Antoni (Frontiers in Genetics, 2020)
Objective: To assess the impact of extensive prenatal genetic counseling on the attitudes and preferences towards first-line prenatal testing for fetal aneuploidy detection. Methods: This is a randomized open-label study, of pregnant women undergoing first trimester combined screening for aneuploidies. Women were divided into the intervention and control groups in a 1:1 design. The intervention consisted of 15-minute extensive counseling about other prenatal testing methods than first trimester combined screening. The main outcome was the desire to choose an invasive testing as their primary prenatal testing option which was measured as absolute risk. Results: After excluding those with incomplete data, 75 women remained in the intervention group and 75 as controls. If given the opportunity, 59% of pregnant women would like to be able to choose the prenatal test that suits their needs. The cell-free DNA (cfDNA) test was the first choice in both groups (51% intervention vs. 63% control group). Women receiving extensive counseling were 32% more likely to choose invasive prenatal testing as their first-line option, reducing the first-trimester combined screening by 20% and cfDNA by 12%. Conclusions: Pregnant women given extensive prenatal counseling on the different aneuploidy testing methods are more likely to choose invasive testing as their first-line test in spite of the concerning risks, although cfDNA would be still maintained as the most chosen option. Registry: ClinicalTrials.gov under the ID: NCT04119349.